Adjuvant and salvage radiotherapy after neoadjuvant therapy and radical prostatectomy for high‐risk localized prostate cancer - Ravi, Praful; Kwak, Lucia; Devlies, Wout; Xie, Wanling; Chipidza, Fallon; Yang, Xiaoyu; Bubley, Glenn; Kaplan, Irving; Kibel, Adam S.; Nguyen, Paul; Taplin, Mary‐Ellen (The Prostate, 2024)
Background We sought to describe patterns of delivery of adjuvant (aRT) and salvage RT (sRT) in patients who underwent RP after receiving neoadjuvant androgen receptor pathway inhibitor (ARPI) before radical prostatectomy (RP) for high‐risk localized prostate cancer (HRLPC). Methods Two hundred eighteen patients treated on phase 2 neoadjuvant trials between 2006 and 2018 at two academic centers were evaluated. aRT and sRT were defined as receipt of RT with a PSA of ≤0.1 or >0.1 ng/mL, respectively. Primary outcomes were biochemical recurrence (BCR), defined as time from aRT/sRT to a PSA rising to >0.1 ng/mL, and metastasis‐free survival (MFS) after RT. Results Twenty‐three (11%) and 55 (25%) patients received aRT and sRT respectively. Median PSA at start of aRT and sRT was 0.01 and 0.16 ng/mL, and median duration from RP to RT was 5 and 14 months, respectively. All aRT patients had NCCN high‐risk disease, 30% were pN1 and 43% had positive surgical margins; 52% had prostate bed RT. Fifty‐one percent of sRT patients had biopsy Gleason 9–10, 29% were pT2 and 9% had positive surgical margins; 63% had RT to the prostate bed/pelvis. At a median follow‐up of 5.3 and 3.0 years after aRT and sRT, 3‐year freedom from BCR was 55% and 47%, and 3‐year MFS was 56% and 53%, respectively. Conclusions aRT was infrequently used in patients who received neoadjuvant ARPI before RP for HRLPC. Outcomes of aRT and sRT were similar but generally poor. Studies evaluating intensified systemic therapy approaches with postoperative RT in this high‐risk population are needed.